Ionic Toxicity Assessment of Water Sources and their Suitability for Irrigation, Drinking, Livestock and Industrial Purposes - Chowdhury1 and Mirza Hasanuzzaman2*, M. S. I. Khan1, M.A. Razzaque1, M.T.I. (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> A study was conducted to assess of the degree of ionic toxicity on the basis of standard criteria for irrigation, drinking, livestock, poultry, aquaculture and industrial purposes of 20 ground water sources in Kushtia, Bangladesh. The chemical analysis included pH, electrical conductivity (EC), total dissolved solids (TDS) and major ionic constituents like Ca, Mg, K, Na, Fe, Mn, B, As, Cu, PO4, CO3, HCO3, SO4 and Cl. sodium adsorption ratio(SAR), soluble sodium percentage (SSP), residual sodium carbonate(RSC) and hardness(HT) were also calculated. The pH (6.93 to 7.63) showed slightly acidic to neutral.Ca (23.8 to 100.2 mg L-1), Mg (20.3 to 57 mg L-1), Na (16.49 to 52.30 mg L-1), K (0.36 to 5.76 mg L-1), HCO3 (132.51 to 347.30 mg L-1) and Cl- (36.9 to 76.2 mg L-1) were predominant along with Mn, Cu and B in lesser amounts. Fe, As, PO4, SO4 and CO3 were found trace to little amounts. The TDS was rated as ‘fresh water’. EC and SAR were ‘medium’ and ‘high salinity’ (C2 and C3) classes and ‘low alkali hazard’ (S1) class, combinedly expressed as C2S1 and C3S1. SSP was of ‘excellent’, ‘good’ and ‘permissible’ categories. Waters were free from RSC and belonged to ‘suitable’ category for irrigation. The waters were classified as ‘hard’, ‘very hard’ and ‘medium hard’ based on hardness (HT).The toxicities of B, Mn and Cl were not found in the study area for irrigation but HCO3, CO3, Fe and As toxicities were found in some sources. Iron content of 7 samples was ‘unsuitable’ for drinking, livestock, poultry and 7 samples were unsuitable for aquaculture usage. Manganese content of all samples was ‘suitable’ for drinking and livestock consumption. Both Fe and Mn content of all samples were ‘problematic’ for industrial usage. Arsenic status of 9 water samples was ‘suitable’ for drinking. Chloride content most of the samples was ‘toxic’ for livestock but all samples were ‘unfit’ for aquaculture. Sulphate of all samples was ‘suitable’ for drinking, livestock, poultry, aquaculture and industrial usage.